Assessment of transient elastography (FibroScan) for diagnosis of fibrosis in non-alcoholic fatty liver disease: A systematic review and meta-analysis - Seyyedabbas Hashemi; Seyyedmoayed Alavian; Mohammad Gholami-Fesharaki (Caspian Journal of Internal Medicine, 2016)
Background: Transient elastography (TE) is a new modality for the diagnosis of liver fibrosis caused by various etiologies. This study was conducted to determine the accuracy of TE in detecting the different stages of liver fibrosis in non-alcoholic fatty liver disease (NAFLD) patients.